Risk of adverse outcomes in patients with underlying respiratory conditions admitted to hospital with COVID-19: a national, multicentre prospective cohort study using the ISARIC WHO Clinical Characterisation Protocol UK - Bloom, CI; Drake, TM; Docherty, AB; Lipworth, BJ; Johnston, SL; Nguyen-Van-Tam, JS; Carson, G; Dunning, J; Harrison, EM; Baillie, JK; Semple, MG; Cullinan, P; et al. (Lancet, 2021)
BACKGROUND: Studies of patients admitted to hospital with COVID-19 have found varying mortality outcomes associated with underlying respiratory conditions and inhaled corticosteroid use. Using data from a national, multicentre, prospective cohort, we aimed to characterise people with COVID-19 admitted to hospital with underlying respiratory disease, assess the level of care received, measure in-hospital mortality, and examine the effect of inhaled corticosteroid use.